2012
DOI: 10.1371/journal.pone.0039524
|View full text |Cite
|
Sign up to set email alerts
|

Novel Root-Fungus Symbiosis in Ericaceae: Sheathed Ericoid Mycorrhiza Formed by a Hitherto Undescribed Basidiomycete with Affinities to Trechisporales

Abstract: Ericaceae (the heath family) are widely distributed calcifuges inhabiting soils with inherently poor nutrient status. Ericaceae overcome nutrient limitation through symbiosis with ericoid mycorrhizal (ErM) fungi that mobilize nutrients complexed in recalcitrant organic matter. At present, recognized ErM fungi include a narrow taxonomic range within the Ascomycota, and the Sebacinales, basal Hymenomycetes with unclamped hyphae and imperforate parenthesomes. Here we describe a novel type of basidiomycetous ErM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 71 publications
1
83
0
Order By: Relevance
“…2e; cf. [37]). The microscopic screening of the hand sections showed that most of the colonies emerging from root segments actually developed from intracellular melanized microsclerotia occurring in the P. oceanica root hypodermis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2e; cf. [37]). The microscopic screening of the hand sections showed that most of the colonies emerging from root segments actually developed from intracellular melanized microsclerotia occurring in the P. oceanica root hypodermis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SSU (18S) ribosomal DNA (rDNA) was amplified using the NS1 + NS24 primer pair [34], ITS1-5.8S-ITS2 rDNA using the ITS1F + ITS4 primer pair [34,35] and LSU (28S) rDNA using the LR0R + LR5 primer pair [36]. For PCR parameters and gel electrophoresis, see [37]. PCR products were purified and sequenced by Macrogen Europe Laboratory (Macrogen Inc., The Netherlands/South Korea) using the NS1, NS4, NS5 and NS24, ITS1F, and LR0R primers.…”
Section: Microscopic Observationsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) of semi-thin hand sections was performed using a FEI Quanta 200 scanning electron microscope in the ESEM mode at low temperatures (−6°C to −3°C). The protocol for transmission electron microscopy (TEM) was the same as in Vohník et al (2012), the Spurr Resin-embedded and uranyl acetate and lead citrate-contrasted samples were observed using a JEOL 1011 microscope equipped with a digital TEM camera (Veleta, Olympus). Photographs were modified for clarity as needed and assembled into Figures using Paint.net ver.…”
Section: Microscopymentioning
confidence: 99%
“…We are only aware of one report on isolation of a serendipitoid mycobiont from Ericaceae hair roots, but this isolate (Sebacinales sp. JPK 89; GenBank JQ926170) soon lost its viability, preventing its use in re-synthesis experiments (Vohník et al 2012a). Sebacinales sp.…”
Section: Introductionmentioning
confidence: 99%